Complexity of Territorial Marketing Based on Citizen Involvement - Alaoui, Yasmine (Current Topics on Business, Economics and Finance Vol. 2, 2023)
The purpose of this study is to investigate how local authorities, particularly municipalities, should focus on the local population when developing territorial strategies. The study of governance falls within the scope of research on the transformation of local public action and on new forms of multi-level and multi-associates coordination: what roles do the devices and tools, in this case marketing in the fabric of local governance, play for a successful attractiveness, and how can governance be promoted on the basis of an endogenous strategy? The primary goal of this document is to provide a tool that allows for in-depth reflection on better ways to strengthen territorial governance. It outlines the pertinent concerns and offers to make a contribution to the design of territorial governance, which is characterised as "the set of methods and tools enabling the coordination, participation and learning of actors and the piloting of territorial projects" [1].